Preparation method of composite material photovoltaic frame profile
By combining a hybrid system formed by graphene, talc and chopped fibers with DCPD resin, the problems of linearity control and lateral tensile properties of composite photovoltaic frame profiles are solved, and the high performance and low cost of the profile are achieved Production and has good aging resistance.
Patent Information
- Application Number
- CN202411598333.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing composite photovoltaic frame profiles have problems in linearity control and lateral tensile properties, and the commonly used resin matrix is not resistant to ultraviolet and acid-base aging, resulting in increased production costs and environmental pollution.
A mixed system formed by the interaction of graphene, talc and chopped fibers is used as a precursor, mixed with DCPD resin, and a dense cross-linked mesh structure is formed through two high-pressure molds to improve the lateral tensile performance and anti-aging properties of the profile. .
Without affecting the linearity of the profile, the lateral tensile performance and bending resistance of the profile are significantly improved, production costs are reduced, and the resulting products are not required to deal with and spray. The resulting products have good UV and corrosion resistance.
Smart Images

Figure CN119458971A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing a composite material photovoltaic frame profile. Background Art
[0002] Composite photovoltaic frame profiles are a new type of material that is synthesized by co-extrusion of a reinforcement composed of fiber-reinforced materials and resin. Currently, the commonly used profile reinforcements in the industry mainly include reinforcements made of a mixture of yarn and other materials and reinforcements made of yarn alone. The defects are as follows: The profile reinforcement is made of a mixture of yarn and felt cloth or a mixture of yarn and multi-axial fabric, which is cured and formed after being fully impregnated with resin. This production method is affected by the width of the felt cloth, the width of the fabric and the gram weight, which can easily lead to difficulty in controlling the straightness of the profile, a low rate of qualified products, and increased production costs.
[0003] The profile reinforcement is made entirely of yarn that is fully impregnated with resin and then cured and formed; although this production method solves the problem of difficulty in controlling straightness, it will result in poor lateral tensile strength and bending performance of the profile. When this type of frame is used for loading testing or punching and mortising, lateral tearing is very likely to occur, and the quality stability is poor, causing great losses to customers.
[0004] In addition, in addition to the reinforcement, the resin matrix commonly used in the industry is polyurethane resin, epoxy resin or unsaturated resin. This type of resin contains benzene rings and is not resistant to UV, acid and alkali aging. The profile must be surface treated again and sprayed with an aging-resistant coating, which increases time and production costs. At the same time, the spraying process has extremely high requirements on equipment and personnel, and is very likely to cause environmental pollution. Summary of the invention
[0005] In view of the deficiencies in the prior art, the problem to be solved by the present invention is: to provide a method for preparing a composite photovoltaic frame profile. The present invention can improve the lateral tensile performance of the product without affecting the straightness of the product, and does not require subsequent processing and spraying, thereby reducing production costs. At the same time, the obtained product has good UV resistance and corrosion resistance.
[0006] The technical solution adopted by the present invention to solve its technical problem is: The method for preparing the composite photovoltaic frame profile of the present invention comprises the following steps: (1) The yarn is arranged with a yarn guide plate and then sent into the first high-pressure mold cavity, and then DCPD resin and catalyst are added to the first high-pressure mold cavity for impregnation, and then a curing is performed to obtain a primary product; (2) sandblasting and dust removal of the primary product to obtain a frosted product; reacting talcum powder, graphene and chopped fibers to prepare a precursor, and mixing the precursor with a DCPD resin to obtain a mixed resin; (3) The frosted product is placed in the second high-pressure mold cavity, and then the mixed resin is added into the second high-pressure mold cavity to coat the surface of the frosted product and perform secondary curing to obtain a composite photovoltaic frame profile.
[0007] in: In the step (1), the yarn is TCR glass yarn, the catalyst is Grubbs second-generation catalyst, and the molar ratio of DCPD resin to catalyst is 10000:0.5-1.5. The manufacturer of Grubbs second-generation catalyst is Hubei Shineng Chemical Technology Co., Ltd.
[0008] The one-time curing in step (1) is divided into three stages of curing, wherein the temperature of each stage is 120-160°C, 140-180°C and 140-200°C respectively.
[0009] In the step (2), the sandblasting is performed by spraying with quartz sand, the mesh size of the quartz sand is 30-120 meshes, and the dust removal is performed by high-pressure air blowing and electrostatic dust removal.
[0010] In the step (2), the chopped fibers are TCR glass yarn sheared fibers, and the average length of the chopped fibers is 0.5-5 mm.
[0011] In the step (2), the precursor is prepared by adding ethylene glycol to talcum powder, graphene and chopped fibers for reaction, and the mass ratio of graphene, talcum powder, chopped fibers and ethylene glycol is 10-30:10-30:10-30:100.
[0012] The reaction time in step (2) is 1.5-2.5 hours, and the reaction temperature is 170-190°C.
[0013] In the step (2), the mass ratio of the precursor to the DCPD resin is 1-30:100, the mixing temperature is 25-30° C., and the mixing time is 30-60 min.
[0014] In the step (3), the secondary curing is a three-stage curing, wherein the temperature of each stage is 120-160°C, 140-180°C and 140-200°C respectively.
[0015] The injection pressure of the first high-pressure mold cavity and the second high-pressure mold cavity is 0.5-1.5MPa.
[0016] The wall thickness of the primary product accounts for 50-70% of the total wall thickness of the composite photovoltaic frame profile.
[0017] The yarn is arranged through a yarn guide plate and sent into the first high-pressure mold cavity so that the yarn is evenly distributed in the first high-pressure mold cavity. Subsequently, DCPD resin and a catalyst are added for infiltration and curing to obtain a primary product. The primary product serves as a base to ensure the basic performance of the profile during subsequent processing. The surface of the primary product is sandblasted and dusted to increase the roughness of the surface of the primary product. During secondary curing, the adhesion between the primary product and the DCPD resin can be increased to make the profile more stable.
[0018] When preparing the precursor, the three raw materials of graphene, talcum powder and chopped fibers are prepared in a certain proportion. The three raw materials are fully mixed and reacted after high temperature and continuous stirring. The excellent lamellar structure of graphene provides excellent crack propagation inhibition for the profile in the XY axis direction; after the chopped fibers react with graphene, they can pass through the graphene single atom-CC-layer in the Z axis direction and form a similar cross-linked network structure with graphene. This structure improves the mechanical tensile properties of the precursor in the Z axis direction; the talcum powder component is a monoclinic system, and the crystal is a pseudo-hexagonal or rhombus flaky shape with strong adsorption. During the precursor synthesis process, the fully dispersed talcum powder will be filled into the cross-linked network structure formed by graphene and chopped fibers, and its filling effect further increases the toughness and shear and tensile strength of the precursor in the three-dimensional direction. After the three raw materials are mixed and reacted, they can promote each other, and the reinforcement effect is greatly improved. Subsequently, the precursor is added to the DCPD resin to perform secondary curing on the frosted product to obtain a composite photovoltaic frame profile. After secondary curing, the dense cross-linked network structure formed by the precursor and DCPD resin after high-temperature treatment can enhance the overall structural stability and mechanical properties of the profile. In addition, due to the excellent performance of DCPD resin, the profile is not easy to age when exposed to ultraviolet light, thereby protecting the profile.
[0019] The beneficial effects of the present invention are as follows: The present invention forms a mixed system through the interaction of graphene, talcum powder and chopped fibers, improves the transverse tensile performance and bending resistance of the profile, when preparing the precursor, the chopped fibers can be better randomly distributed in the graphene structure due to the indefinite size, and then the gap between the two is filled with talcum powder, which increases the disorder of the profile structure, so that the force received by the profile in all directions is more uniform, the overall structure of the profile is more stable, the mechanical properties are more excellent, and the service life is longer. The proportion of graphene, talcum powder and chopped fibers can also be adjusted to obtain profiles with different tensile strengths; since the secondary curing is integrated molding, the structure of the outer layer of the profile is the same as the internal structure, and both are dense cross-linked network structures, and due to the thermal stability and light stability of the DCPD resin itself, the profile can resist ultraviolet and is not easy to age, and there is no need to add a protective layer to the surface of the profile, and the profile integrated structure can avoid the situation of stratification or shedding of the protective layer, and the stability is better and the anti-aging effect is better. The use of two curing moldings and the use of high temperature conditions can increase the overall firmness of the profile and avoid the situation of profile stratification. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a process flow chart of the present invention; Figure 2 A schematic cross-sectional view of a composite material profile produced by the method of the present invention; Figure 3 An enlarged view of a partial cross section of a composite material profile produced by the method of the present invention.
[0021] In the figure: 1. Wire board; 2. First high-pressure mold cavity; 3. Sandblasting area; 4. Second high-pressure mold cavity; 5. Traction area; 6. Cutting area; 201, preforming area; 202, first curing area; 301, dust removal area; 401, second curing area. DETAILED DESCRIPTION
[0022] The present invention is further described below with reference to the embodiments.
[0023] Example 1 like Figure 1-3 As shown, the method for preparing the composite photovoltaic frame profile of the present invention comprises the following steps: (1) 120 TCR glass yarns were arranged by a yarn guide plate 1 and sent into the first high-pressure mold cavity 2, and then DCPD resin and Grubbs second-generation catalyst were added to the first high-pressure mold cavity 2 at a pressure value of 1 MPa at a molar ratio of 10000:1 for impregnation, and then three temperatures were set at 140°C, 160°C, and 180°C for primary curing to obtain a primary product; (2) The primary product is sent to the sandblasting zone 3 and sandblasted with 30-mesh quartz sand, followed by high-pressure air blowing and electrostatic dust removal to obtain a frosted product; talcum powder, graphene, chopped fibers of 2mm TCR glass yarn and ethylene glycol are reacted at a mass ratio of 20:20:20:100 at 180° C. for 2 h to prepare a precursor, and the dried precursor is mixed with DCPD resin at a mass ratio of 1:100, and stirred at 25° C. for 30 min until completely dispersed to obtain a mixed resin; (3) The frosted product is placed in the second high-pressure mold cavity 4 with a pressure value of 1 MPa, and then the mixed resin is added into the second high-pressure mold cavity 4 to coat the surface of the frosted product and perform secondary curing at three temperatures of 140°C, 160°C, and 180°C to obtain a composite photovoltaic frame profile.
[0024] The composite photovoltaic frame profile is drawn by the drawing area 5 and enters the cutting area 6 to be cut into a composite photovoltaic frame of a suitable length. The wall thickness of the initial product is 1.2 mm, and the total wall thickness of the composite photovoltaic frame profile is 2 mm.
[0025] like Figure 1 As shown, along the pultrusion direction of the yarn, from left to right are the wire board 1, the preforming area 201, the first high-pressure mold cavity 2, the first curing area 202, the sandblasting area 3, the dust removal area 301, the second high-pressure mold cavity 4, the second curing area 401, the traction area 5 and the cutting area 6.
[0026] When preparing composite photovoltaic frame profiles, the yarn is first introduced into the wire board 1 for combing, then pre-processed in the preforming area 201 and then sent to the first high-pressure mold cavity 2 for glue injection to obtain a primary product. The primary product enters the sandblasting area 3 for spraying quartz sand and is purged with high-pressure air and electrostatically precipitated in the dust removal area 301 to obtain a frosted product. The surface of the frosted product is rough to facilitate better subsequent bonding.
[0027] The frosted product enters the second high-pressure mold cavity 4 for glue injection, and then enters the second curing area 401 for secondary curing. After the secondary curing, the composite photovoltaic frame profile is prepared and enters the cutting area 6 under the traction of the traction area 5 to be cut into a composite photovoltaic frame of appropriate length.
[0028] Example 2 like Figure 1-3 As shown, the method for preparing the composite photovoltaic frame profile of the present invention comprises the following steps: (1) 150 TCR glass yarns were arranged by a yarn guide plate 1 and sent into the first high-pressure mold cavity 2, and then DCPD resin and Grubbs second-generation catalyst were added to the first high-pressure mold cavity 2 at a molar ratio of 10000:1.5 at a pressure value of 1.5 MPa, and then three temperatures were set at 120°C, 140°C, and 180°C for primary curing to obtain a primary product; (2) The primary product is sent to the sandblasting zone 3 and sandblasted with 60-mesh quartz sand, followed by high-pressure air blowing and electrostatic dust removal to obtain a frosted product; talcum powder, graphene, 3mm TCR glass yarn chopped fibers and ethylene glycol are reacted at a mass ratio of 15:15:15:100 at 190° C. for 1.5 h to prepare a precursor, and the dried precursor is mixed with a DCPD resin at a mass ratio of 30:100, and stirred at 30° C. for 60 min until completely dispersed to obtain a mixed resin; (3) The frosted product is placed in the second high-pressure mold cavity 4 with a pressure value of 1.5 MPa, and then the mixed resin is added into the second high-pressure mold cavity 4 to coat the surface of the frosted product and perform secondary curing at three temperatures of 120°C, 140°C, and 180°C to obtain a composite photovoltaic frame profile.
[0029] The composite photovoltaic frame profile is drawn by the drawing area 5 and enters the cutting area 6 to be cut into a composite photovoltaic frame of a suitable length. The wall thickness of the initial product is 1.3 mm, and the total wall thickness of the composite photovoltaic frame profile is 2.5 mm.
[0030] Example 3 like Figure 1-3 As shown, the method for preparing the composite photovoltaic frame profile of the present invention comprises the following steps: (1) 180 TCR glass yarns were arranged by a yarn guide plate 1 and sent into the first high-pressure mold cavity 2, and then DCPD resin and Grubbs second-generation catalyst were added to the first high-pressure mold cavity 2 at a molar ratio of 10000:0.5 at a pressure value of 0.5 MPa, and then three temperatures were set at 160°C, 180°C, and 200°C for primary curing to obtain a primary product; (2) The primary product is sent to the sandblasting zone 3 and sandblasted with 120 mesh quartz sand, followed by high-pressure air blowing and electrostatic dust removal to obtain a frosted product; talcum powder, graphene, 1.2 mm TCR glass yarn chopped fibers and ethylene glycol are reacted at a mass ratio of 30:30:30:100 at 170° C. for 2.5 h to prepare a precursor, and the dried precursor is mixed with a DCPD resin at a mass ratio of 15:100, and stirred at 25° C. for 45 min until completely dispersed to obtain a mixed resin; (3) The frosted product is placed in the second high-pressure mold cavity 4 with a pressure value of 0.5 MPa, and then the mixed resin is added into the second high-pressure mold cavity 4 to coat the surface of the frosted product and perform secondary curing at three temperatures of 160°C, 180°C, and 200°C to obtain a composite photovoltaic frame profile.
[0031] The composite photovoltaic frame profile is drawn by the drawing area 5 and enters the cutting area 6 to be cut into a composite photovoltaic frame of a suitable length. The wall thickness of the initial product is 1.5 mm, and the total wall thickness of the composite photovoltaic frame profile is 2.2 mm.
[0032] Comparative Example 1 No precursor is added during the pultrusion process, and the remaining steps are the same as in Example 1.
[0033] Comparative Example 2 The precursor only uses graphene, and the remaining steps are the same as in Example 1.
[0034] Comparative Example 3 The precursor only uses talcum powder, and the remaining steps are the same as in Example 1.
[0035] Comparative Example 4 The precursor only uses chopped fibers, and the remaining steps are the same as in Example 1.
[0036] Comparative Example 5 Only talc and graphene were added to the precursor.
[0037] Talc, graphene and ethylene glycol were reacted at a mass ratio of 30:30:100 at 180° C. for 2 h to prepare a precursor, and the dried precursor was mixed with DCPD resin at a mass ratio of 1:100, and stirred at 25° C. for 30 min until completely dispersed to obtain a mixed resin. The remaining steps were the same as in Example 1.
[0038] Comparative Example 6 Only graphene and chopped fibers are added to the precursor.
[0039] Graphene, chopped fibers and ethylene glycol were reacted at a mass ratio of 30:30:100 at 180° C. for 2 h to prepare a precursor, and the dried precursor was mixed with a DCPD resin at a mass ratio of 1:100, and stirred at 25° C. for 30 min until completely dispersed to obtain a mixed resin. The remaining steps were the same as in Example 1.
[0040] Comparative Example 7 Only talc and chopped fibers were added to the precursor.
[0041] Talc, chopped fibers and ethylene glycol were reacted at a mass ratio of 30:30:100 at 180° C. for 2 h to prepare a precursor, and the dried precursor was mixed with DCPD resin at a mass ratio of 1:100, and stirred at 25° C. for 30 min until completely dispersed to obtain a mixed resin. The remaining steps were the same as in Example 1.
[0042] Comparative Example 8 The resin used is epoxy pultrusion resin, and the remaining steps are the same as those in Example 1.
[0043] Comparative Example 9 The resin used is polyurethane pultrusion resin, and the remaining steps are the same as those in Example 1.
[0044] Data Analysis: 1. The composite photovoltaic frame profiles produced in Examples 1-3 and Comparative Examples 1-7 were tested for transverse tensile properties. The results are shown in Table 1.
[0045]
[0046] 2. The anti-aging performance of the composite photovoltaic frame profiles produced in Examples 1-3 and Comparative Examples 8-9 was tested. The results are shown in Table 2.
[0047]
[0048] 3. The composite photovoltaic frame profiles produced in Examples 1-3 and Comparative Examples 8-9 were tested for alcoholysis resistance. The results are shown in Table 3.
[0049]
[0050] From the above, it can be seen that the composite material photovoltaic frame profile prepared by the present invention has a transverse tensile strength of more than 80 MPa, a strength retention rate of resistance to ultraviolet aging of more than 89%, and a strength retention rate of resistance to alcoholysis of more than 94%. Combining various data, it can be seen that the composite material photovoltaic frame profile obtained by the present invention has superior performance, higher transverse tensile strength, and good aging resistance and alcoholysis resistance.
Claims
1. A method for preparing a composite photovoltaic frame profile, characterized in that: The following steps are involved: (1) The yarn is arranged with a yarn guide plate and then sent into the first high-pressure mold cavity, and then DCPD resin and catalyst are added to the first high-pressure mold cavity for impregnation, and then a curing is performed to obtain a primary product; (2) sandblasting and dust removal of the primary product to obtain a frosted product; reacting talcum powder, graphene and chopped fibers to prepare a precursor, and mixing the precursor with a DCPD resin to obtain a mixed resin; (3) The frosted product is placed in the second high-pressure mold cavity, and then the mixed resin is added into the second high-pressure mold cavity to coat the surface of the frosted product and perform secondary curing to obtain a composite photovoltaic frame profile.
2. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: In step (1), the yarn is TCR glass yarn, the catalyst is Grubbs second generation catalyst, and the molar ratio of DCPD resin to catalyst is 10000:0.5-1.
5.
3. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: The one-time curing in step (1) is divided into three stages of curing, wherein the temperature of each stage is 120-160°C, 140-180°C and 140-200°C respectively.
4. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: In step (2), the sandblasting is performed by spraying quartz sand, the mesh size of the quartz sand is 30-120 meshes, and the dust removal is performed by high-pressure air blowing and electrostatic dust removal.
5. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: In step (2), the chopped fibers are TCR glass yarn sheared fibers, and the average length of the chopped fibers is 0.5-5 mm.
6. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: In step (2), the precursor is prepared by adding ethylene glycol to talcum powder, graphene and chopped fibers for reaction, and the mass ratio of graphene, talcum powder, chopped fibers and ethylene glycol is 10-30:10-30:10-30:
100.
7. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: The reaction time in step (2) is 1.5-2.5 hours, and the reaction temperature is 170-190°C.
8. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: In step (2), the mass ratio of the precursor to the DCPD resin is 1-30:100, the mixing temperature is 25-30° C., and the mixing time is 30-60 min.
9. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: The secondary curing in step (3) is a three-stage curing, wherein the temperature of each stage is 120-160°C, 140-180°C and 140-200°C respectively.
10. The method for preparing the composite photovoltaic frame profile according to claim 1, characterized in that: The wall thickness of the initial product accounts for 50-70% of the total wall thickness of the composite photovoltaic frame profile.